The influence of over endorsement on purchase intentions is mediated by the authenticity and credibility of influencers on social media influencers on Tiktok - aulia, Della; Thabrani, Gesit (Universitas Negeri Padang, 2024)
Currently, many social media influencers make over endorsements so that it can reduce the perception of authenticity and expertise of the influencer, which in turn affects the intention to buy the endorsed product. This research was conducted with the aim of analyzing how the influence of Over Endorsement influences Purchase Intentions, with Influencer Authenticity and Credibility as mediating factors, on Social Media Influencers on Tiktok. The subjects of this research are people who use TikTok and show interest in products or services that are often endorsed by influencers in West Sumatra. The research participants totaled 200 respondents selected as samples. Data was collected through online distribution of questionnaires via Google Form, and then analyzed using SmartPLS software. The results of this study reveal that (1) Influencer authenticity has a significant positive influence on purchase intention, and (2) Influencer credibility has a significant positive influence on purchase intention (3) Over endorsement has a negative influence on influencer authenticity (4) Over endorsement has negative influence on influencer credibility. (5) Over Endorsement mediated by influencer authenticity and credibility on purchase intentions has a negative influence.